Towards Professional Decision‐Making: A Vignette Study on Problem Behaviour in Flemish, Lithuanian and Latvian Foster Children. - Coster, Matthias De; Vanderfaeillie, Johan; West, Delphine; Verheyden, Camille; Pigozne, Tamara; Pivorienė, Jolanta; Holen, Frank Van (Child & Family Social Work, 2026)
As directives are often missing or fragmented, foster care workers have a huge amount of discretionary power. They are trusted to use this power for the benefit of the foster families they monitor. Wrong decisions must be prevented at all times. With greater understanding of the factors affecting decision‐making, this can be done for the specific part of professional practice that is about providing extra support for foster children and/or for their foster parents. A total of 297 Flemish, Lithuanian and Latvian foster care workers participated in a study set up to examine what factors affect foster care workers' decisions regarding problem behaviour. Three case factors, five decision‐maker factors and one external factor were of influence. Professional decision‐making entails case factors to be (come) most decisive. Systematic and standardised screening for emotional and behavioural problems and low parenting quality could help diminish other factors' impact.